HUBUNGAN KEDISIPLINAN DAN KOMPETENSI PROFESIONAL DENGAN KINERJA GURU SEKOLAH DASAR DI KECAMATAN TARUMAJAYA KABUPATEN BEKASI - Nuralih; Gusti Yarmi; Kadarisman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the relationship between discipline and professional competence in the performance of elementary school teachers in Tarumajaya District, Bekasi Regency. The study population involved 431 teachers from 26 public elementary schools, and the sample was determined using a cluster random sampling technique of 138 teachers. This study uses a quantitative approach with regression analysis to identify the influence of independent variables, namely discipline and professional competence, on the dependent variable, namely teacher performance. The results of the study showed a significant positive relationship between discipline and teacher performance (R = 0.673) and professional competence and teacher performance (R = 0.879). The combination of discipline and professional competence explained 77.2% of the variation in teacher performance (R² = 0.772). These results emphasize the importance of discipline in creating an organized learning environment and professionalism in improving teaching effectiveness. This study provides important implications for developing educational policies, especially in the training and developing teacher discipline and professional competence. Investment in these two aspects is expected to significantly improve teacher performance, support the achievement of educational goals, and improve the quality of student learning.